Anorexia nervosa e internet: uma análise comportamental de um blog pró-anorexia - Santos, Daniela Resende dos (2011)
The objective of the present research was to analyze a pro-anorexia blog indentifying the control relationships between the blog manager and the users of it. In order to do so, at first all posted messages by the manager and the commentaries by the readers were categorized and later the relationships between the verbal responses were analyzed. For each theme introduced by the manager s messages and by the blog users commentaries it was verified whether there was agreement/repetition or disagreement by the other readers. Forty four themes in seven messages and 605 commentaries were identified. The majority of the themes could be classified in pro-anorexia and anti-anorexia themes. The pro-anorexia theme more frequently observed on the manager s messages was the reported negative feelings related to being fat . However the most commented by the readers was the fact that anorexia is a sickness which causes pain and death. The manager s messages accompanied by photos were followed by the major number of commentaries. Among the most used persuasion resources by the manager are the artifices of strength as caps lock, italics and bold. The majority (77, 4%) of the readers identified themselves with female nicknames. One may come to the conclusion that mutual verbal control occurred, once the readers questioned the manager, asked more information and extra blog contact and the manager replied directly some readers